Middle Eastern Terrorism : From Black September to September 11 - Ensalaco, Mark (Book collections on Project MUSE., 2008)
Since the first airplane hijacking, Middle Eastern terrorists have sacrificed innocent human lives in the name of ideology, and terrorism has emerged as the most important security concern of our time. Ensalaco has written a thoroughly researched narrative account of the origins of Middle Eastern terrorism, addressing when and why terrorists started targeting Americans and American interests and what led to the September 11 attacks. The author reveals the changing motivations from secular Palestinian nationalism to militant Islam and demonstrates how competition among terrorists for resources and notoriety has driven them to increasingly extreme tactics. As he argues, terrorist attacks grew from spectacle to atrocity. Although the face of terrorism has changed, its nature has not. Acts of terror are war crimes, and terrorism is a crime against humanity.